The Constructivist Approach to Student's Metacognitive Formation - Abi Krisna Arasit (IJEDR: Indonesian Journal of Education and Development Research, 2023)
Success in education and learning is determined by the willingness and ability of students in designing and planning learning. The ability to plan, design, implement, and evaluate learning is included in metacognition. The urgency in the research is that not all teachers are able to design a learning approach for the development of students' metacognitive abilities. Some of the learning approaches implemented by the teacher are still not applicable. If this is allowed, it will have an impact on students' low metacognition. The type of research used is pre-experimental One Group Pre-test – Post Test Design. The research target schools were 186 Bandar Lampung State Elementary Schools. The sample was taken by stratified random sampling, namely SD with an Accreditation so that 40 State Elementary Schools were obtained. The research subjects were students in grades 1, 2 and 3 in each sample school. The results showed that the constructivist approach can improve students' metacognitive abilities. Students who have high metacognitive abilities can develop knowledge, find ideas, conclude lessons, develop problem solving strategies, estimate time estimates, have high creativity and have independence in learning.